Juventude, educação e movimentos sociais: relações entre conhecimentos escolares e saberes socais dos jovens de ensino médio no interior de uma escola de assentamento/PA - AVIZ, Larissa de Nazaré Carvalho de (Universidade Federal do Pará, 2017)
The research aims to analyze the integration/fragmentation between social knowledge produced by young Palmares II settlement and school Knowledge, the class struggle perspective in the educational environment of higt school teaching Growing in Practice- Para. The research was carried out with the youth of the 3rd year of high school in 2015 and had the locus School Growing up in practice, located in Palmares II settlement in the municipality of Parauapebas- PA. Methodologically research maintains a qualitative approach of a case study. It is the main tool for data collection, semi-structured interview. Interviews were conducted in two stages: the first in a group of 12 young people was interviewed for about 50 minutes in order to select respondents of the interview would focus on guiding questions and the second were interviewed five young subjects who were selected for this research, two boys and three girls. Data from these interviews were analyzed based on the analysis of the content. A reference on the method, is based on the Historical and Dialectical Materialism, which enabled the understanding of the studied reality, where the contradiction and historicity categories had their importance for the realization of this study. Thus, the raids showed that: there is a certain gap between high school institutionalized from the Secretariat of State intervention Education -SEDUC / PA that space constituted and claimed by the social movement. Through this institutionalization was given a fragmented teaching-learning process, exclusionary, based solely on fulfilling the modules.